Accumulation of Senescent Neural Cells in Murine Lupus With Depression-Like Behavior - Saito, Yuki; Miyajima, Maki; Yamamoto, Sena; Sato, Tsukasa; Miura, Norihiro; Fujimiya, Mineko; Chikenji, Takako S. (Frontiers in Immunology, 2021)
Neuropsychiatric manifestations targeting the central, peripheral, and autonomic nervous system are common in systemic lupus erythematosus (SLE); collectively, these symptoms are termed neuropsychiatric SLE (NPSLE). Among a wide variety of neuropsychiatric symptoms, depression is observed in about 40% of SLE patients. Several cytokines and chemokines have been identified as biomarkers or therapeutic targets of NPSLE; in particular, the levels of type 1 interferons, TNFs, and IL-6 are elevated in SLE patient’s cerebrospinal fluid (CSF), and these factors contribute to the pathology of depression. Here, we show that senescent neural cells accumulate in the hippocampal cornu ammonis 3 (CA3) region in MRL/lpr SLE model mice with depressive behavior. Furthermore, oral administration of fisetin, a senolytic drug, reduced the number of senescent neural cells and reduced depressive behavior in the MRL/lpr mice. In addition, transcription of several senescence and senescence-associated secretory phenotype (SASP) factors in the hippocampal region also decreased after fisetin treatment in the MRL/lpr mice. These results indicate that the accumulation of senescent neural cells in the hippocampus plays a role in NPSLE pathogenesis, and therapies targeting senescent cells may represent a candidate approach to treat NPSLE.